Agricultural value chain finance for smallholder farmers [Rwanda] - Kwizera, Alice (Technical Centre for Agricultural and Rural Cooperation, 2018)
A project in Rwanda's Kirehe district has targeted smallholder farmer and their cooperatives to help them leverage private investment and funds from financial institutions, and with this help them upgrade and diversify their activities. Finance for participants across seven agricultural value chains in the district has resulted in the construction of processing plants, greenhouses, warehouses and drying facilities